Stress Heterogeneity and Slip Weakening of Faults under Various Stress and Slip - Longjun Dong; Qiaomu Luo (Geofluids)
The rock mass of deep underground engineering is in the complex geological environment of high stress, high temperature, and high water pressure. In the process of deep mining and underground space development, the fault-slip seismic source may cause engineering accidents with strong destructive capacity. An in-depth study of fault slip characteristics is very important in the engineering disaster prevention and control. In this paper, a slip model was established based on the finite element software ABAQUS. A total of 20 loading ways are set for various stress and slip, which include the possible slip conditions of fast slip, slow slip, and critical state. By comparing the simulation diagrams and collecting the data of representative grid elements on the loading surface and slip surface, the slip characteristics such as stress heterogeneity under different loads are analyzed. The results show that the increase of slip velocity will make the slip unstable, and the local stress and deformation will become irregular. The spatial stress heterogeneity and the resulting local high working rate will lead to the decrease of the friction strength and the slip weakening. These results can provide some useful suggestions for the research of seismic activities caused by fault slip.